2012
DOI: 10.1155/2012/693717
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 Prevents MPP+-Induced Apoptosis in PC12 Cells by Stimulating Estrogen Receptors with Consequent Activation of ERK1/2, Akt and Inhibition of SAPK/JNK, p38 MAPK

Abstract: Ginsenoside Rb1 shows neuroprotective effects in various neurons, including dopaminergic cells. However, the precise mechanisms of action are uncertain. In this paper, we examine whether Rb1 has a neuroprotective effect on MPP+-induced apoptosis and attempt to clarify the signaling pathway in PC12 cells. Apoptosis of PC12 cells was determined by DNA fragmentation assay, the activation of caspase-3, or by the inactivation of Bcl-xL. Rb1 inhibited MPP+-induced caspase-3 activation and DNA fragmentation and activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 30 publications
3
51
0
Order By: Relevance
“…Many compounds in SMI have been reported to exhibit various potential neuroprotective effects, including the antioxidant effects of Ginsenoside Rg1 , the anti-inflammatory effects of Ginsenoside Re (Lee et al 2012), the anti-apoptotic and anti-autophagic effects of Ginsenoside Rb1 (Chen et al 2010;Lu et al 2011;Hashimoto et al 2012) and the anti-excitotoxic effects of schizandrin (Cheng et al 2008). Previously, we confirmed that SMI inhibited cerebral ischemia/reperfusioninduced brain injury and the expression of tissue factors ).…”
Section: Introductionsupporting
confidence: 62%
“…Many compounds in SMI have been reported to exhibit various potential neuroprotective effects, including the antioxidant effects of Ginsenoside Rg1 , the anti-inflammatory effects of Ginsenoside Re (Lee et al 2012), the anti-apoptotic and anti-autophagic effects of Ginsenoside Rb1 (Chen et al 2010;Lu et al 2011;Hashimoto et al 2012) and the anti-excitotoxic effects of schizandrin (Cheng et al 2008). Previously, we confirmed that SMI inhibited cerebral ischemia/reperfusioninduced brain injury and the expression of tissue factors ).…”
Section: Introductionsupporting
confidence: 62%
“…A previous study has shown that Rb1 can exert a suppressive effect on local inflammation in rats with cerebral ischemia [9]. Furthermore, Rb1 protects PC12 cells from apoptosis through stimulation of the oestrogen receptor [10]. However, no data yet has been reported concerning the effect of Rb1 on apoptosis and inflammation in chondrocytes or its therapeutic role in OA.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most active ingredients of ginseng, Rb1 has been reported to have a variety of pharmacological effects, including anti-inflammation, anti-apoptosis, anti-oxidation, increasing endothelial cell nitric oxide production, and inhibiting angiogenesis, mainly through asso-ciation to androgen or estrogen receptors (5,14,17,23,43). Our previous study has shown that Rb1 pretreatment inhibits LPS-induced leukocyte adhesion to microvascular wall and interstitial mast cell degranulation (39), which are implicated in vascular hyperpermeability (19,38), suggesting a protective role of Rb1 against vascular protein leakage.…”
mentioning
confidence: 99%